Water Resources Planning, Development and Management - Wurbs, Ralph (IntechOpen, 2013)
This book is a collection of innovative up-to-date perspectives on key aspects of water resources planning, development, and management of importance to both professional practitioners and researchers. Authors with outstanding expertise address a broad range of topics that include planning strategies, water quality modeling and monitoring, erosion prediction, freshwater inflows to estuaries, coastal reservoirs, irrigation management, aquifer recharge, and water allocation.